Accuracy of pediatric advanced life support method for predicting the depth of endotracheal tube in Indonesian children (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND The pediatric advanced life support (PALS) method can predict the depth of endotracheal tube (ETT) in pediatric patients easily, but it has limitations due to variations in the children’s characteristics, especially the racial consideration. This study compared the accuracy of ETT depth prediction based on the PALS methods in Indonesian children. METHODS Patients aged 0–12 years, who underwent elective surgery with oral intubation, were recruited consecutively based on their ages: 0–24 months and 25 months–12 years for this cross-sectional study in Cipto Mangunkusumo Hospital, Jakarta, Indonesia from June to August 2014. Bland–Altman analysis was used to compare the two measurement methods: PALS method to predict the ETT depth accuracy and auscultation method to confirm the position of the ETT. Furthermore, correlation analysis was done to examine the relationship of age, weight, height, and ETT internal diameter with ETT depth. RESULTS 50 patients were recruited in each group. Bland–Altman test of ETT depth in the 0–24 months age group showed a 1.18 cm mean difference from confirmation using the auscultation method (limits of agreement −0.71 to 3.08). The 25 months–12 years age group showed a 1.11 cm mean difference with limits of agreement were −0.95 to 3.17 from confirmation using the auscultation method. Age and weight had the strongest correlation value to ETT depth in the 25 months–12 years age group (R2 = 62.3%). CONCLUSIONS The PALS method is inaccurate for predicting ETT depth in Indonesian children aged 0–12 years old compared with the auscultation method.